Feeding on Exudates and Leaves of Cassava Cultivars with Varying Cyanogenic Potentials: Implications for the Biology of Typhlodromalus aripo, a Key Biocontrol Agent of Cassava Green Mite in Africa - Famah Sourassou, Nazer; Agboka, Komi; Negloh, Koffi; Hanna, Rachid; Tchabi, Atti (European Scientific Journal, ESJ, 2025)
The predatory mite Typhlodromalus aripo, a key biological control agent of the cassava green mite in Africa, is known to feed on cassava exudates and, in the absence of prey, directly on cassava leaves. While cassava cultivars differ greatly in cyanogenic potential (CNP), the consequences of feeding on exudates and leaves from cultivars with different CNP levels for T. aripo biology remain unknown. We conducted laboratory experiments to evaluate several life history parameters of T. aripo on exudates and leaf discs of three cassava cultivars – TME1 (low CNP), TMS91934 (moderate CNP), and TMS82/00661 (high CNP). T. aripo completed its development on exudates of all three cultivars, being faster with higher survival on exudate of TMS82/00661 (6.8 days, 68.2%) compared with TME1 (7.9 days, 53.8%) and TMS91934 (8.2 days, 56.8%). None of the exudates supported oviposition, although adult female survivorship was highest on TMS82/00661. T. aripo was unable to develop beyond the deutonymph stage on the leaf discs of all three cassava cultivars. However, juvenile and adult longevity were greater on TME1 compared with the two other cultivars. Exudates were free of cyanogenic glycosides with similar amino acid concentrations; however, sugar content was twice as high in exudates of TMS8200661 compared with the other cultivars. These findings highlight the importance of cassava exudate quality for predator persistence and biological control success.